2019
DOI: 10.1007/978-3-030-02568-7_212
|View full text |Cite
|
Sign up to set email alerts
|

How do Emotions Influence Brand Attachment? The Mediation Role of Brand Authenticity: An Abstract

Abstract: In time of uncertainty, brand authenticity is seen as one of the major factors of brand success. Both academics and practitioners have come to the conclusion that brand authenticity has become an essential trait of the brand in times when consumers are overwhelmed with product offerings. This research examines the impact of emotions on brand attachment by studying the mediating role of perceived brand authenticity. In-store emotions and consumption emotions have been taken into consideration. A multifaceted co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Authenticity has become one of the common words used in modern advertising, with both marketers and ad agencies convinced that execution of an authentic ad is key to effective advertising and brand success (Morhart et al, 2015;Hallem et al, 2019). Specifically, prior research has suggested that authenticity provides a competitive edge in crowded marketplaces (Hallem et al, 2019), stimulates brand trust (Anderberg and Morris, 2006), helps and moderates emotional attachment to a brand (Hallem et al, 2019), is key to the success of cause-related marketing partnerships (Kotler et al, 2012) and helps consumers find genuineness, truth and virtue within their mix of consumption goals (Michael and Beverland, 2010). Authentic advertising can help create personal brand resonance and helps overcome consumer scepticism about advertising.…”
Section: Literature Review and Hypotheses Development The Concept Of mentioning
confidence: 99%
See 2 more Smart Citations
“…Authenticity has become one of the common words used in modern advertising, with both marketers and ad agencies convinced that execution of an authentic ad is key to effective advertising and brand success (Morhart et al, 2015;Hallem et al, 2019). Specifically, prior research has suggested that authenticity provides a competitive edge in crowded marketplaces (Hallem et al, 2019), stimulates brand trust (Anderberg and Morris, 2006), helps and moderates emotional attachment to a brand (Hallem et al, 2019), is key to the success of cause-related marketing partnerships (Kotler et al, 2012) and helps consumers find genuineness, truth and virtue within their mix of consumption goals (Michael and Beverland, 2010). Authentic advertising can help create personal brand resonance and helps overcome consumer scepticism about advertising.…”
Section: Literature Review and Hypotheses Development The Concept Of mentioning
confidence: 99%
“…It is widely claimed that authenticity is a major driver of advertising success (Hallem et al, 2019;Becker et al, 2019). However, it is not clear what authenticity means in different contexts and situations.…”
Section: Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation